Conditional Mediation of Absorptive Capacity and Environment in International Entrepreneurial Orientation of Family Businesses - Hernández-Perlines, Felipe; Xu, Wenkai (Frontiers in Psychology, 2018)
This study analyzes the effect of conditional mediation of environment-absorptive capacity in international entrepreneurial orientation of family businesses. Results involve data from 218 Spanish family businesses, analyzed with SmartPLS 3.2.7 software. This paper presents a relevant contribution both to the academic field and the performance of family firms, helping to understand the process of transforming international entrepreneurial orientation into a better international performance through absorptive capacity while family businesses invest their efforts in aligning international entrepreneurial orientation and absorptive capacity with international results, bearing in mind the positive moderator effect of environment. The most relevant contribution of this work is to integrate in the same model the mediating effect of the absorption capacity and the moderating effect of the environment: the effect of the international entrepreneurial orientation on the international performance of family businesses improves with the mediation of the absorptive capacity (the variability of international performance goes from 32.5% to 40.6%) and the moderation of the environment (to variability of international performance goes from 40.6% to 45.3%).